High performance all-solid-state Li–Se battery based on selenium loaded on Ti3C2 MXene cathode - Renbo Liu; Chongxing Li; Qingyu Li; Shuxian Zhang; Chengxiang Wang; Zhiwei Zhang; Yuanchang Shi; Lidong Yang; Longwei Yin; Rutao Wang (Green Energy and Resources, 2024)
Selenium has high theoretical volumetric capacity of 3253 mAh cm−3 and acceptable electronic conductivity of 1 × 10−5 S m−1, which is considered as a potential alternative to sulfur cathode for all-solid-state rechargeable batteries with high energy density. However, the development of all-solid-state Li–Se batteries (ASSLSBs) are hindered by sluggish kinetics and poor cycling life. In this work, trigonal Se nanocrystallines are homogenously distributed in the interspace and on the surface of MXene layers (denoted as Se@MXene composite) by a novel melt-diffusion method. ASSLSBs based on this Se@MXene composite cathode exhibit large specific capacity of 632 mAh g−1 at 0.05 A g−1, high-rate capability over 4 A g−1, and excellent cycling stability over 300 cycles at 1 A g−1. The ex-situ analytical techniques demonstrate that the excellent electrochemical performance of Se@MXene cathode largely arises from structural stability with the assistance of conductive MXene and reversible redox behavior between Li2Se and Se during the repeating charge/discharge process. Our study points out the potential of material design of Se cathode based on conducting 2D materials with good electrochemical behavior, which may accelerate the practicability of ASSLSBs.